PREPARING PRESCHOOL CHILDREN FOR READING AND LITERACY - Makhmudova Madinakhan Sobirkhanovna; Ismailova Ehtibarkhan (Galaxy International Interdisciplinary Research Journal, 2024)
To pronounce sounds correctly and to identify and form ideas about the sound composition of words. Understanding vowels and consonants. Development of phonemic perception and imagination based on teaching to distinguish voiced and unvoiced sounds. Creating sentences around this next sentence, thus continuing the work of perfecting the message and finishing it, acquires a great educational and educational value in terms of developing connected speech. The educational aspect is that children acquire additional knowledge and skills in logically connecting one sentence to another, using lexical and grammatical tools. The educational aspect can be seen in the fact that the sentences are meaningful and impressive.